2020
DOI: 10.1093/icvts/ivaa306
|View full text |Cite
|
Sign up to set email alerts
|

Biological versus mechanical aortic valve replacement in non-elderly patients: a single-centre analysis of clinical outcomes and quality of life

Abstract: OBJECTIVES The aim of this study was to evaluate short- and long-term clinical outcomes, including the perceived health-related quality of life, in patients younger than 65 years having undergone aortic valve replacement either with biological or mechanical valve prostheses. METHODS Between 2002 and 2013, 242 consecutive patients <65 years of age underwent isolated aortic valve replacement at our institution, either wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Most studies showed the risk of re-intervention is higher in bioprostheses although the risk of major bleeding is lower. However, the long-term survival benefits remain controversial with some studies demonstrating a survival benefit with mechanical valves ( 26 28 ) while some did not ( 29 32 ). Although the survival benefits could be due to primary valve failure, which could be less of an issue due to the advancement of TAVR, particularly in patients who are at high risk for a redo of SAVR.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies showed the risk of re-intervention is higher in bioprostheses although the risk of major bleeding is lower. However, the long-term survival benefits remain controversial with some studies demonstrating a survival benefit with mechanical valves ( 26 28 ) while some did not ( 29 32 ). Although the survival benefits could be due to primary valve failure, which could be less of an issue due to the advancement of TAVR, particularly in patients who are at high risk for a redo of SAVR.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical valves may offer longer durability but require lifelong anticoagulation with a potential risk of bleeding or pannus formation with leaflet restriction depending on the adequacy of anticoagulation. 6 In contrast, bioprosthetic valves have been associated with greater risk of structural valve deterioration (SVD), especially in younger patients, and with reduced overall survival in patients younger than 50 years. 7 , 8 The potential of valve-in-valve therapies may reduce the need for redo MVR, thereby impacting the likelihood of younger patients receiving a bioprosthetic valve.…”
mentioning
confidence: 99%
“…The general study characteristics are presented in Table 1 and in Table S1 (Supplementary Materials) . In total, 16 studies from 11 countries were included, 12 of which reported results from PMS cohorts [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], and a further 4 studies reported results from multivariate analysis [ 24 , 25 , 26 , 27 ]. Of those studies, only one was RCT study [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, as shown in Table 4 , 111 studies reported that more frequent reoperation was required for patients with BVs. Finally, three studies showed no significant difference in terms of complications observed between the two groups [ 13 , 14 , 16 ]. The three studies which showed better survival outcomes for the MV group compared to BV group were for patients aged 50–70 years.…”
Section: Resultsmentioning
confidence: 99%